The Effect of Anger Management Skills on Occupational Violence and Aggression in Midwives Working in Zanjan Medical Centers: A Quasi-experimental Study - Roya Nasiri Almas; Elham Jafari; Roghieh Khorghani (Hamadan University of Medical Sciences, 2024)
Background and Objective: Workplace violence against health workers is a global problem, with a high prevalence among midwives. The study aimed to determine the effects of anger management skills on occupational violence and aggression in midwives working in Zanjan medical centers. Materials and Methods: The study was a quasi-experimental intervention. From all the midwives working in the hospitals of Zanjan, 46 people were selected using the convenience sampling method and were divided into intervention (n=23) and control (n=23) groups through a stratified random-blocked method. The intervention group participated in eight 60-minute online sessions of anger management training. The research tools included the Negative Acts Questionnaire and the Ahvaz Aggression Questionnaire. The data were analyzed using repeated measurement tests. Results: Before the intervention, there were no statistically significant differences in the score of occupational violence and aggression between the two groups. The occupational violence and aggression were significantly lower in the intervention group than in the control group immediately after the intervention and in the six-week follow-up (P˂0.05). The changes in occupational violence (measured change of 47.1%) and aggression (measured change of 37.7%) were not statistically significant between the groups after adjustment with the baseline variables. Moreover, the changes in aggression subscales were not significant. Conclusion: Anger management training did not lead to sustained reductions in occupational violence and aggression against midwives. Therefore, it seems necessary to carry out more and advanced interventions in this field.